Phylogenetic relationships based on nuclear and plastid DNA sequences reveal recent diversification and discordant patterns of morphological evolution of the Chilean genera of Gilliesieae (Amaryllidaceae: Allioideae) - Escobar, Inelia (2020)
Gilliesieae are a South American tribe of Amaryllidaceae characterized by high floral diversity. Given different taxonomic interpretations and proposals for generic and specific relationships, a representative phylogenetic analysis is required to clarify the systematics of this group. The present study provides a framework for understanding phylogenetic relationships and contributing to the development of an appropriate taxonomic treatment of Gilliesieae. Molecular analyses, based on nuclear (ITS) and plastid DNA sequences (trnL-F and rbcL), resolve with strong support the monophyly of the tribe and the differentiation of two major clades. Clade I comprises the genera Gilliesia, Gethyum and Solaria and Clade II includes Miersia and Speea. These well-supported clades are mostly congruent with vegetative and karyotype characters rather than, e.g., floral symmetry. At the generic level, all molecular analyses reveal the paraphyly of Gilliesia and Miersia. Gethyum was found to be paraphyletic, resulting in the confirmation of Ancrumia as a distinct genus. Several instances of incongruent phylogenetic signals were found among data sets. The calibrated tree suggests a recent diversification of the tribe (Pliocene–Pleistocene), a contemporary process of speciation in which instances of hybridization and incomplete lineage sorting could explain patterns of paraphyly and incongruence of floral morphology.